Evaluation of maize (Zea mays L.) hybrids for growth, yield and yield attributing traits in Rampur, Chitwan, Nepal - Dhakal, Krishna Hari (Journal of Agriculture and Natural Resources, 2025)
Hybrid maize plays a crucial role in enhancing maize productivity in Nepal due to its higher yield potential and superior agronomic performance compared with open-pollinated varieties. The objective of this study was to identify high-yielding maize hybrids suitable for winter planting under the Terai conditions of Nepal. A total of ten maize hybrids were evaluated in a randomized complete block design with three replications during the winter season of 2024-25 at Rampur, Chitwan. The results revealed significant differences (p<0.01) among hybrids for growth parameters, including days to 50% anthesis, days to 50% silking, plant height, and ear height. Yield and yield-attributing traits, such as thousand-kernel weight, number of kernel rows per ear, number of kernels per row, cob length, and cob diameter, were also found significantly affected by hybrid differences (p<0.01). The highest grain yield was recorded for KWM92/KWM93 (10,076 kg ha-1), followed by KWM91/KWM93 (9,892 kg ha-1), Winner (NMH8352) (9,878 kg ha-1), CML581/CML582 (9,168 kg ha-1), and CML581/CML612 (8,778 kg ha-1). These results indicate that the identified hybrids possess high yield potential and can be promoted as promising candidate hybrids for winter maize production in the Terai region of Nepal.